Considerations on plastic surgery in Santiago de Cuba - Meilyn Ricardo Ramírez; Leonor Ramírez Quesada (Centro Provincial de Información de Ciencias Médicas, 2021)
The problem of dissagrement of the human being with the specific characteristics of his body may have its origin in an esthetical problem or in a purely physical character affair which limits, in a marked way, the development of his daily activities. Both may be solved through a surgery, specially, a esthetic surgery. The objective of this work is to reaffirm that the plastic esthetic surgery solves real physical or mental health problems, so as to recognize  the work of plastic surgery specialists as evaluators  and advisers of patients visiting the provincial department who look for help. National and international literature on the topic was reviewed and it was concluded that plastic surgery with esthetic aims is a solution, as it satisfies the expectatives either from people searching treatment, as from the specialists who give the service.